Evaluation on the efficacy of microbial approaches in the control of Ganoderma boninense and their effects to soil microbial diversity - Arnnyitte Alexander; Chong, Khim Phin (Universiti Malaysia Sabah, 2014)
Basal Stem Rot (BSR) is the most destructive disease of oil palm (Elaeis guineensis Jacq.) which caused by bracket fungus; Ganoderma boninense. With no remedy to date, this disease has jeopardized the industry of oil palm critically. Several approaches including cultural, chemical, mechanical and biological measures have been reported in attempt to control this disease, but unfortunately, none have given satisfactory result. Therefore, a more reliable approach that could manage this disease, besides a continuous and sustainable oil palm production is worth to be further investigated. Introduction of microbes in disease management have been used for decades. An astute observation of low incidence of disease due to Ganoderma pathogen in natural ecosystem suggests that a healthy natural ecosystem can hinder the incidence of Ganoderma pathogen outbreak. In this respect, study on the potential of microbes in suppressing the growth of Ganoderma boninense and its effect to the soil microbial diversity were investigated in this project. Three microbes-based products which are Living Soil Microbes (LSM), Agrinos (AGN) and Agriorganica (AO) were tested in this study. LSM contains multi-strain of Bacillus spp. and Trichoderma spp., whereas AGN consist of Bacillus spp., Pseudomonas spp. and Aspergillus sp. Meanwhile, AO comprises of three living food microbes which are Lactobacillus, Nattobacillus and Saccharomyces cerevisiae developed from Japanese fermentation and brewing technology. To examine the ability of the treatments in reducing BSR disease incidence, assessments in nursery and field trial were conducted. The results from both trials showed that LSM, AGN and AO were able to reduce the colonization of G. boninense based on the reduction of ergosterol content compared to untreated control.